2007
DOI: 10.1002/ptr.2191
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of Chinese medicine on fibroblast viability: implications in wound healing

Abstract: Diabetes mellitus has been a clinical problem for hundreds of years. Over 194 million people suffer from this disease worldwide. Improper control of diabetes may result in diabetic foot ulcer or even amputation. Granulation formation is an important issue essential for ulcer healing. The CRL-7522 fibroblast cell line and primary fibroblasts from a diabetic foot ulcer patient were used to model the wound healing enhancing activities of two clinically efficacious Chinese herbal formulae, Formula 1 (F1) and Formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
(20 reference statements)
1
25
0
3
Order By: Relevance
“…Fibroblasts secrete collagens and subsequently affect the remodeling of granulation tissue into mature dermis (Lau et al, 2007). In this study, results of BrdU incorporation and MTT assays revealed that silymarin had no effect on fibroblast proliferation in the studied concentration range.…”
Section: Discussionmentioning
confidence: 52%
“…Fibroblasts secrete collagens and subsequently affect the remodeling of granulation tissue into mature dermis (Lau et al, 2007). In this study, results of BrdU incorporation and MTT assays revealed that silymarin had no effect on fibroblast proliferation in the studied concentration range.…”
Section: Discussionmentioning
confidence: 52%
“…Radix Rehmanniae has been shown to greatly facilitate fi broblast proliferation in our laboratory and also in some other studies [3][4][5]. Astragalus is well known for its immunomodulating effects.…”
Section: Discussionmentioning
confidence: 61%
“…The herbs mainly worked on the control of infl ammation and promotion of granulation formation through stimulation of fi broblast proliferation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is an important worldwide public health problem, affecting 5-10% of the population and impairing the quality of life of the affected individuals due to the significant resulting complications (Lau et al 2007;Vojtassák et al 2006;Sweitzer et al 2006).…”
Section: Introductionmentioning
confidence: 99%